2019
DOI: 10.1111/apt.15511
|View full text |Cite
|
Sign up to set email alerts
|

Declining hospitalisation and surgical intervention rates in patients with Crohn's disease: a population‐based cohort

Abstract: Summary Background Lifetime risk of surgery in patients with Crohn's disease remains high. Aim To assess population‐level markers of Crohn's disease (CD) in the era of biological therapy. Methods Population‐based cohort study using administrative data from Ontario, Canada including 45 235 prevalent patients in the Ontario Crohn's and Colitis Cohort (OCCC) from 1 April 2003 to 31 March 2014. Results CD‐related hospitalisations declined 32.4% from 2003 to 2014 from 154/1000 (95% confidence interval (CI) [150, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
3
23
1
Order By: Relevance
“…Therefore, our study suggests that the increase in the use of biological drugs was associated to a reduction in the need for surgery and hospitalization due to complications, although causality cannot be concluded. These data from a large population-based health register of clinical practice, along with the data recently published by Rahman A, et al [ 19 ] in a population-based study from Ontario between 2003 and 2014 (Canada), corroborate previous data obtained in the clinical trials reported above [ 7 , 8 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, our study suggests that the increase in the use of biological drugs was associated to a reduction in the need for surgery and hospitalization due to complications, although causality cannot be concluded. These data from a large population-based health register of clinical practice, along with the data recently published by Rahman A, et al [ 19 ] in a population-based study from Ontario between 2003 and 2014 (Canada), corroborate previous data obtained in the clinical trials reported above [ 7 , 8 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, we found a decrease in the likelihood of repeated ED visits in patients who were being treated with biologics for IBD, indicating that appropriate IBD treatment may reduce the risk of repetitive visits and potentially translate to appreciable cost-savings. Consistent with this, Rahman et al found that rates of hospitalizations, ED visits, and inpatient surgeries markedly declined for Crohn’s patients in Ontario from 2003 to 2014, while rates of biologic medication use increased [ 28 ]. This information is reassuring; repeat ED visits are less likely to be for IBD and appropriate IBD treatment seems to play a role in preventing repeat visits.…”
Section: Discussionmentioning
confidence: 81%
“…65 In a population-based study from Ontario, Canada, CD-related hospitalizations decreased by 32% from 154/1,000 patients in 2003 to 104/1,000 patients in 2014. 72 In the SK-IBD cohort, the cumulative risks of hospitalization at 1, 5, 10, and 20 years after CD diagnosis were 31.2%, 40.7%, 51.9%, and 67.9%, respectively. 30 The cumulative risk of hospitalization was significantly lower in the recent cohort than in the older cohort, with the 5-year cumulative risk of hospitalization being 52.2% in the 1986-2003 cohort and 36.6% in the 2004-2015 cohort.…”
Section: ) CDmentioning
confidence: 91%
“…The cumulative risks of hospitalization in the SK-IBD cohort were similar to or slightly lower than those in Western population-based cohort studies. 33,65,71,72…”
Section: ) CDmentioning
confidence: 99%